Efeito da angiotensina (1-7) na função renal em um modelo experimental de injúria renal aguda - Roberta da Silva Filha (2015)
Paraquat (PQ), a potent herbicide, due to its high toxicity has been associated to high mortality levels after human exposure and to significant organ damages. Some evidences indicate that PQ is a nephrotoxic agent which may be responsible for progressive renal lesions. However, few studies have investigated the acute effects of the herbicide on renal function and structure. The aim of this study was to evaluate the structural and functional changes and the effect of angiotensin (1-7) (Ang (1-7)) on the renal damage induced by PQ. Male Wistar rats (230 - 300 g) were divided into 8 groups: groups NaCl (CTL) and NaCl - Ang (1-7) received 0,9% NaCl through intraperitoneal route (ip) and groups PQ and PQ - Ang (1-7) received PQ (20 mg/kg, ip). Four hours after injection of PQ, groups NaCl - Ang (1-7) and PQ - Ang (1-7) received Ang (1-7) (10 and 50 μg/kg, intragastrically, ig). After 24 h of PQ exposure, animals were anesthetized and blood and urine samples were collected for analysis of renal function and kidney were removed for histological analysis and indirect quantification of neutrophils, macrophages and lipid peroxidation. Our results showed that PQ affected renal parameters under study by increasing serum creatinine (mg/dl) (from 0.27 ± 0.02, n = 7, CTL, to 0.48 ± 0.06, n = 10), which reflected in a decrease in the glomerular filtration rate (Liters/24h) (from 2.05 ± 0.16, n = 7, CTL, to 0.96 ± 0.11, n = 10), and elevated fractional excretion (%) of Na+ (from 0.25 ± 0.03, n = 7, CTL, to 0.97 ± 0.14, n = 7) and K+ (from 37.1 ± 1.1, n = 7, CTL, to 103.6 ± 29.8, n = 10). Urine flow (Liters/24h) and proteinuria (mg/24h) were also increased by PQ (from 0.006 ± 0.000, n = 7, CTL, to 0.014 ± 0.001, n = 10, and from 1.35 ± 0.21, n = 7, CTL, to 7.58 ± 0.70, n = 10, respectively). In addition, PQ increased the urine excretion of renal gamma GT enzyme (U/L) (from 10.1 ± 1.8, n = 7, CTL, to 107.2 ± 25.4, n = 10), and renal concentration of lipid hydroperoxides (μM) (from 0.48 ± 0.04, n = 6, CTL, to 3.52 ± 0.39, n = 7). No beneficial effect of Ang (1-7) was detected on the major renal damages under investigation, exception fot the attenuation of urinary excretion of the enzyme gamma GT (group PQ, 107.2 ± 25.4, n = 10 vs group PQ - Ang (1-7)10, 6.4 ± 2.7 U/L, n = 7), and for a decrease in renal lipid peroxide concentration (group PQ, 3.52 ± 0.39, n = 7 vs group PQ - Ang (1-7)50, 2.13 ± 0.08 μM, n = 7). The data suggest an Ang (1-7) protective effect on the renal damages induced by PQ.